On Ginberg's "Howl" and Miguel Labordeta's shout - Calvo Carilla, José Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper studies the links between the Beat Generation poet Allen Ginsberg and the Spanish poetry of the sixties, paying particular attention to the role played in it by the poets Carlos Edmundo de Ory and Miguel Labordeta.
Keywords: Beat Generation; Allen Ginsberg; Carlos Edmundo de Ory